Diguanylate Cyclases in Vibrio cholerae: Essential Regulators of Lifestyle Switching - Biswas, Sumit; Chouhan, Om Prakash; Bandekar, Divya (Frontiers in Cellular and Infection Microbiology, 2020)
Biofilm formation in Vibrio cholerae empowers the bacteria to lead a dual lifestyle and enhances its infectivity. While the formation and dispersal of the biofilm involves multiple components – both proteinaceous and non-proteinaceous, the key to the regulatory control lies with the ubiquitous secondary signaling molecule, cyclic-di-GMP (c-di-GMP). A number of different cellular components may interact with c-di-GMP, but the onus of synthesis of this molecule lies with a class of enzymes known as diguanylate cyclases (DGCs). DGC activity is generally associated with proteins possessing a GGDEF domain, ubiquitously present across all bacterial systems. V. cholerae is also endowed with multiple DGCs and information about some of them have been pouring in over the past decade. This review summarizes the DGCs confirmed till date in V. cholerae, and emphasizes the importance of DGCs and their product, c-di-GMP in the virulence and lifecycle of the bacteria.